Therapeutic Evaluation of Neemazal® Against Experimental Eimeria Tenella Infection in Broiler Chickens, Jos - Nigeria - Goni, Abraham Dogo; Bi-Allah, Bukar Markus; Emmanuel, Vandi Tizhe; Gloria, Pisha Karaye; David, Oshadu; Paul, Abdu (Journal of Parasite Research, 2020)
Coccidiosis in poultry is caused by protozoan parasites of the Eimeria species, which is responsible for worldwide economic losses. The aim of this study was to evaluated the therapeutic effect of NeemAzal® on Eimeria tenellain broiler Chickens as compared to Amprolium as a standard anticoccidial drug. A total of One Hundred and Sixty (160) broiler chicks were purchased, acclimatized and randomly divided into 4 groups (G1, G2, G3 & G4). G1 non-infected, non-treated (negative control), (G2) infected with 20000 E. tenella oocysts (positive control), (G3) infected and treated with Amprolium (Standard, 7 mg/kg b.w. for 5 days) and (G4) infected and treated with NeemAzal®200 mg/kg b.w. for 5 days). Evaluation was by clinical signs, performance data (weight gain, oocyst shed/gram faeces (OPG) and histopathology of the Caecum, Liver and Kidney. The data showed that birds infected with E. tenellahad an output of 1.3×105±3,333 oocysts per gram faeces on day 5 post inoculation. This output is significantly decreased to 0.37×105±3,111 oocysts in neem-treated birds. Infection with E. tenellainduced marked histopathological alterations in the caecum in the form of inflammation, vacuolation of the epithelium, and destruction of some villi. NeemAzal® decrease body weight loss of infected chickens. Moreover, the number of goblet cells stained with Hematoxylin and Eosin (H&E) within the infected villi was significantly lowered (P≤0.05). The results revealed that chicks of G1 had the best performance data compared to G2, G3& G4. In G3 & G4 there were a remarkable improvement in the data on performance, clinical signs, gross and microscopically caecal lesions compared to G2. Amprolium (G3) was shown to be superior to NeemAzal® (G4) compared to G2. NeemAzal® could be a good alternative for use as a coccidiostat to supplement the expensive anti-coccidiostats in the market.
Keywords: Therapeutic effect; NeemAzal®; Experimental infection; Eimeria tenella; Broiler Chickens; Nigeria